Elucidating pharmacophore of novel NS3 inhibitor for dengue via proteochemometric modeling and molecular dynamics simulation / Zafirah Liyana Abdullah - Abdullah, Zafirah Liyana (Faculty of Pharmacy, 2024)
The global incidence of infectious diseases presents a substantial threat to human health. Among these infections, dengue virus (DENV) has become the most notable and the most rapidly spreading mosquito-borne viral disease1. According to the World Health Organization (WHO), the number of incidences has increased 30-fold from the past 50 years, as well as the geographical expansion of the disease to new countries2. Therefore, the research titled "Elucidating Pharmacophore of Novel NS3 Inhibitor for Dengue via Proteochemometric Modeling and Molecular Dynamics Simulation" is proposed to make contributions to the development of antivirals for dengue infection, a mosquitoborne viral disease that affects millions of people worldwide